PREDICTION OF TEAK BONITA (SITE INDEX) IN CENTRAL JAVA, INDONESIA, BASED ON SOIL PROPERTIES - Chairil Anwar (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2007)
The objective of this study was to determine the most correlated soil and physiographic factor with the site index of teak. Tree height and stand age were recorded from seventy-three plots located in Central Java, Indonesia, to determine site index. Size of each plot was 0.1 ha. Measured site properties measured were percent slope, elevation, slope position, slope length, dominant topographic form, aspect, and thickness of A horizon. Soil samples from A and B horizon were analyzed for soil color, soil texture, available phosphorous, total nitrogen, and organic matter content. Analysis indicated that the site index of teak was positively correlated with thickness of A horizon and westerly aspects, and negatively correlated with clay content of A horizon and elevation. A multiple regression using these variables produced an R2 of 0.55.